THE RELATIONSHIP BETWEEN REACTION SPEED AND BODY COORDINATION IN FOOTBALL GOALKEEPERS - Vapayev Kadam Ravshonbekovich (Proximus Journal Publishing, 2025)
This article provides a scientific analysis of the relationship between reaction speed and body coordination in football goalkeepers. Reaction speed directly influences a goalkeeper’s ability to make quick and effective decisions during the game, while coordination affects the accuracy of catching and jumping movements. The study evaluates goalkeepers' physical fitness, neuropsychological state, and reflex levels through various testing methods. Additionally, the influence of factors such as age, experience and training methodologies on these indicators is examined. The research findings are of great significance for developing effective training programs aimed at improving reaction time and coordination in goalkeepers
Keywords: reaction speed; body coordination; goalkeeper